A desconsideração da personalidade jurídica e seus aspectos processuais - Barbuio, Carlos Otávio Missiato (2019)
This dissertation addresses the legal procedure for the application of disregard of legal entity in local law, referring it as an incident lawsuit which final decision will have mixed effectiveness; declaratory and condemnatory. At first, it refers to the theory of disregard from a material point of view, through the analysis of the empirical origin of the doctrine in the English and American courts. It discuss its development in the scientific sense of foreign law, with the creation of the first theory called Rule-Exception dualism, by ROLF SERICK. Under this heading, such theme is developed considering the main studies about the doctrine in foreign law and moves to a doctrinal analysis about the disregard in local law, with the objective of systematizing such theory. On this point, it is paramount to explain that the purpose of this introductory study is to reveal the premises that served as a foundation for the application of disregard in forensic practice, which is of great importance as the extension of responsibility through the application of the doctrine which has exceptional character. With this observation made, the theme focus in a second moment on the study regarding the application of the theory of disregard of l egal entity in the 1973 Code of Civil Suit, with the objective of comprehending the doctrinal debates which led the legislator to establish a specific procedure for disregarding. In this light, the present work aims to elucidate the theory of disregard of legal entity regarding its procedural aspects - the nature of the lawsuit; the necessity of preserving the principle of the right to a fair hearing; the burden of proof and the limit of the responsibility extension - through doctrinal and jurisprudential research. Finally it must be emphasized that the hypothesis raised, which culminated in the present work consists on comprehending the new normative system as well as verifying the validity of the understanding that (i) the claim has an action nature, which is declaratory and condemnatory; (ii) the need for a prior hearing of the affected person makes it impossible as a rule, to grant injunctions; and (iii) the responsibility extension must be limited to the amount of the alleged loss arising from the unlawful act. This theme, as for the second item above, it involves a complex issue and has relevance since injunctions have the objective of ensuring a useful outcome of the lawsuit and, at the same time, conceding this request violates the fundamental principle of the right to a fair hearing. Regarding the third item, it is noted that the forensic practices allows that a third person to be held liable for the totality of the obligation, which does n ot seem correct insofar as this form of responsibility, in theory should be limited to the amount of the illegal act.